Pengaruh Kualitas Produk Dan Word Of Mouth Terhadap Kualitas Pembelian Skincare Brightening Di Kalangan Remaja Kota Bandung - Fani Khaliatul Komar; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research aims to analyze the influence of product quality and word of mouth on purchasing decisions of brightening skincare among teenagers in Bandung City. The study employed a quantitative approach with causal comparative design. Data were collected through questionnaires distributed online to 90 respondents selected by purposive sampling. The validity and reliability tests confirmed that all questionnaire items were valid and reliable. Multiple linear regression analysis revealed that product quality has a positive and significant effect on purchasing decisions, while word of mouth, although positively related, did not significantly affect purchasing decisions. Simultaneous testing showed that both variables together significantly influence purchasing decisions. These findings provide practical implications for skincare companies to focus on enhancing product quality while optimizing credible word of mouth strategies to target teenage consumers.